The Impact of Hormones on Osteoporosis in Women - Awad, Fayhaa Mohammed (Journal of Science in Medicine and Life, 2025)
Introduction: Osteoporosis significantly affects women's health in Balad. This study investigates the disease's prevalence, management, and prevention using biochemical quantitative tests. Emphasis is placed on understanding the disease's biology, its impact on bone health, and the various factors contributing to its risk, with a particular focus on diet, lifestyle, and urban healthcare strategies. Objective: The main objective of the study is to assess the prevalence of osteoporosis among women in Balad using biochemical tests and bone density assessments, and to identify the key factors that influence the management and prevention of the disease. Materials and Methods: The study was conducted from December 2023 to February 2024 in Balad, involving 120 female participants categorized into three age groups. Blood samples were collected and analyzed using a complete blood count machine to measure several biochemical markers. Bone mass indexes were calculated to correlate physical health with the biochemical data. Results and Discussion: The results showed significant variations in biochemical markers such as WBC, RBC, and platelets across different age groups, indicating a strong impact of age on osteoporosis indicators. The statistical analysis confirmed significant differences, with elevated WBC in older age groups suggesting an inflammatory response, while decreases in RBC and hemoglobin pointed towards potential anemia. Decreased levels of calcium and magnesium were observed with increasing age, emphasizing impaired mineral homeostasis in osteoporosis patients. Conclusion: Osteoporosis in women of Balad is profoundly influenced by age-related changes in biochemical markers. The study highlights the necessity for age-specific treatment protocols and supports the integration of regular biochemical marker monitoring into clinical practice. Recommendations for future research include longitudinal studies to further understand the disease's progression and the development of targeted therapeutic strategies.